The Concept of Disability Reflected in the Textbooks of Jammu and Kashmir Board of School Education - Wani, Hilal Ahmad (THE PRIMARY TEACHER, 2022)
Disability denotes the challenges faced by individuals with impairments due to certain limitations, hindering their equal participation in society compared to those without impairments. In the pursuit of empowering persons with disabilities, India introduced The Rights of Persons with Disabilities (RPwD) Act, 2016, replacing the Persons with Disability Act, 1995, shifting the focus from charity-oriented approaches to rights based initiatives. It guarantees equal opportunities, prohibits discrimination, mandates reasonable accommodations, ensures accessibility, advocates inclusive education, reserves employment opportunities, and offers social security benefits, thereby fostering their active engagement in society. Specifically, addressing education, the RPwD Act, 2016 emphasises inclusive schooling, reasonable accommodations, and equal opportunities for individuals with disabilities. This includes ensuring accessible infrastructure, adapting learning materials, providing specialised support, and training educators to facilitate an inclusive learning environment. For creating an inclusive learning environment, comprehensive integration of the disability concept into textbooks gains paramount importance. This article assesses the integration of disability-related content in primary level textbooks sanctioned by the Jammu and Kashmir Board of School Education (JKBOSE). The study examined JKBOSE textbooks from Class I–V, revealing that while NCERT—adapted books show some inclusivity, JKBOSE-prepared textbooks lack a comprehensive representation of the disability concept. This analysis underscores the need for further enhancements in disability portrayal within educational materials, striving for a more inclusive educational landscape.